2016
DOI: 10.1111/ijlh.12496
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of hypochromic erythrocytes and reticulocyte hemoglobin equivalent predictors of response to intravenous iron in hemodialysis patients

Abstract: % Hypo-He and Ret-He are reliable parameters for the study of erythropoiesis status in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
2
21
0
1
Order By: Relevance
“…The sensitivity, however, was poorer when compared to reported diagnostic iron studies (sensitivity of 90.0%), soluble transferrin receptor (sensitivity of 86%), and recent studies of Ret‐He . Ret‐He has been widely studied, within numerous population groups including pregnancy . The reported diagnostic Ret‐He cutoff values vary from 27 to 32 pg according to the study population and diagnostic inclusion criteria .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The sensitivity, however, was poorer when compared to reported diagnostic iron studies (sensitivity of 90.0%), soluble transferrin receptor (sensitivity of 86%), and recent studies of Ret‐He . Ret‐He has been widely studied, within numerous population groups including pregnancy . The reported diagnostic Ret‐He cutoff values vary from 27 to 32 pg according to the study population and diagnostic inclusion criteria .…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the Ret‐He, the %Hypo‐He reflects the iron status of the RBC over the circulating life span (120 days). While the %Micro‐R has not been well researched as a marker of ID, studies have demonstrated the clinical utility of the %Hypo‐He in several patient groups with ID . For example, the %Hypo‐He is the most recognized parameter for identifying functional ID (iron stores are normal/increased with inadequate iron supply to erythrocytes) in patients with chronic renal failure treated with erythropoietin‐stimulating agents .…”
Section: Introductionmentioning
confidence: 99%
“…Sysmex introduced another measure of hypochromia, %Hypo‐He, which defines red cells with MCH <17 pg. In a previously mentioned study, Urrechaga et al demonstrated the reliability of %Hypo‐He in predicting response to iron supplementation at a diagnostic threshold of 2.4% . Several other studies demonstrate the utility of %HRC and %Hypo‐He in diagnosing iron deficiency and predicting response to intravenous iron treatment in CKD patients …”
Section: Methods Of Iron Quantificationmentioning
confidence: 94%
“…43,44 In a study of 504 subjects with different anemia etiologies, a diagnostic threshold of 25 pg was established to identify iron deficiency (<25 pg) from other forms of anemia. 44 Furthermore, in a study of 40 dialysis patients, Urrechaga et al 45 found RetHe to be a reliable predictor of response to intravenous iron supplementation at a diagnostic threshold of 30.8 pg.…”
Section: Reticulocyte Hemoglobin Content (Equivalent)mentioning
confidence: 99%
“…This indicates that a patient with Ret‐He >27.0 pg is unlikely to have IDA, while allowing for iron supplementation to be initiated in patients with Ret‐He ≤27.0 pg. Given that iron is necessary for effective erythropoiesis, timely and accurate testing of iron status is essential, particularly in certain disease populations . Ret‐He is used as a useful parameter for the monitoring of iron treatment .…”
Section: Discussionmentioning
confidence: 99%